Lamenting Karbala in Europe: Husayni Liturgy and Discourses of Dissent amongst Diasporic Bahraini and Lebanese Shiis - Marei, Fouad Gehad (Islam and Christian-Muslim relations, 2021)
The presence of Shii communities in Europe is increasingly felt, especially as they establish independent religious and social infrastructures. Supporters of different Shii–Islamist political parties have established transnational links connecting diasporic communities with their countries of origin. These links have shaped and been shaped by religious, political and social dynamics in the Middle East. This article examines how lamentation poetry performed in Shii ritual gatherings is used to articulate political dissent among diasporic communities. The lachrymal expressions and descriptions that characterize Shii lamentation poetry have the ritualistic function of metaphorically identifying participants with Imam Husayn and his cause. Organizers of these gatherings, however, use lamentation poetry to narrate and give meaning to geopolitical developments in the Middle East, especially since the Anglo-American invasion of Iraq and the toppling of Saddam Hussein in 2003. This article constitutes the first attempt to examine the political contextualization of Shii lamentation poetry, embedded within the political discourses of two Shii Islamist parties, the al-Wefaq Movement in Bahrain and Hizbullah in Lebanon. Unlike other studies on Shii ritual practices, it is informed by a multi-sited ethnographic study of female-only and male-dominated ritual spaces in the United Kingdom, Sweden, Lebanon, Iraq and Bahrain.